Realist Evaluation of the “Abiye” Safe Motherhood Initiative in Nigeria: Unveiling the Black-Box of Program Implementation and Health System Strengthening - Oladimeji, Olawale J.; Fatusi, Adesegun O. (Frontiers in Health Services, 2022)
Introduction Realist evaluation studies have spanned different aspects of medicine, especially in the field of public health. However, very few of these studies explicitly detailed how program implementation triggered outcomes that could strengthen understanding of its effect on Health System Strengthening in specific settings. In low- and middle-income countries, like Nigeria, there is a paucity of realist evaluation studies, despite the implementation of multiple intervention programs and projects in these countries. This article is aimed at unveiling the black-box of program implementation and Health System Strengthening of the “Abiye” Safe Motherhood Program in Ondo State, Nigeria. Specifically, it identified the role of contextual factors in the “Abiye” program in Ondo State, determined the mechanisms that facilitated or constrained outcomes of the “Abiye” program, and developed a Context Mechanism Outcome (CMO) Configuration from which a Middle Range Theory (MRT) can be framed. Methodology This was qualitative research structured along with the realist domains (Context, Mechanism, and Outcome). The Initial Program Theory was validated by the qualitative study, after which a new MRT was developed. The study population comprised key stakeholders, secondary stakeholders, and primary stakeholders in the Abiye safe motherhood program. Data was collected through 10 key informant interviews, 28 in-depth interviews, and six focus group discussions sessions. Thematic analysis was used to analyze all the qualitative data collected, and seven themes with 19 subthemes emerged in the study. Results We identified 13 contextual factors under five principal areas, with most of the factors playing enabling roles, some playing inhibitory roles, while very few played both roles. We elicited eight mechanisms, and some of these facilitated the outcomes, while some constrained the outcomes of the program. Health system strengthening was a key feature of the outcome of the program. We developed a middle-range theory based on the 6 CMO configurations we elicited from the study. Conclusion and Policy Implications Realist evaluation is an iterative process that looks beyond the surface to generate evidence. By applying the realist approach, we generated pieces of evidence that can be adapted for policymaking in public health interventions in LMIC.